Biocompatible Tin Oxide Nanoparticles: Synthesis, Antibacterial, Anticandidal and Cytotoxic Activities. Issue 14 (10th April 2019) - Rehman, Suriya; Asiri, Sarah Mousa; Khan, Firdos Alam; Jermy, B Rabindran; Khan, Hafeezullah; Akhtar, Sultan; Jindan, Reem Al; Khan, Khalid Mohammed; Qurashi, Ahsanulhaq
Abstract: Biocompatible SnO2 NPs, were synthesized by simple and facile ultrasonic technique, and further studied for antibacterial, anticandidal and invitro cytotoxic activity. The obtained size of synthesized SnO2 NPs, was 5–30 nm and characterized by X‐ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The evaluation of antibacterial and anticandidal activity of the SnO2 NPs, was done by determining the minimum inhibitory concentration (MIC), and minimum bactericidal/fungicidal concentration (MBC/MFC), against Escherichia coli and Candida albicans, respectively. The MIC of 0.5 mg/ml and MBC of >1 mg/ml for E. coli, while as the MIC of 8 mg/ml and MFC >16 mg/ml for C. albicans, was obtained. Maximum activity for both, bacteria and Candida was achieved, however, to the best of our knowledge, this is the first report of anticandidal activity exhibited by SnO2 NPs. Treatment of synthesized SnO2 NPs against the colorectal (HCT‐116) cancer cell line, decreased the cell survivability in a dose‐dependent manner, as lower dose showed decrease of 73.00%, whereas, higher dosage caused a significant 31.34% decrease in the cell viability. The obtained results confirmed, that the prepared SnO2 NPs can be the future broad‐spectrum antibacterial, anticandidal and anticancer agent, and can be further explored for application in the biomedical field. Abstract : SnO2 NPs were synthesized by ultra‐sonochemical method and characterized by XRD, FESEM and TEM analysis. Evaluation of antimicrobial activity was carried out against, E. coli, C. albicans, and HCT‐116 (Human colorectal carcinoma cells) for anticancer activity. The synthesized NPs were found effective against, both the human pathogens and the cancer cells. Therefore, the synthesized NPs hold significant potential for use, in the pharmaceutical and biomedical applications.